PENGARUH PEMBELAJARAN MIND MAPPING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Eva Fitria Ningsih (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the influence of the application of the Mind Mapping learning model on students' mathematical problem-solving ability and students' attitudes towards the Mind Mapping learning model. The research sample consisted of 30 students from the experimental class and 30 students from the control class who came from the population of SMPN 1 Pandeglang. The research method used is a type of experiment. Using the Independent Sample t-test assuming both homogeneous variances (equal variance assumed) with a significance level of 0.05 at the time of the initial test, a significance value on significance (2-tailed) was 0.432 > 0.05 that between the experimental and control classes no significant differences were found. In the final test it was obtained that the significance (2-tailed) was 0.003 > 0.05 thus receiving H1 that the mathematical problem-solving ability of students who used the Mind Mapping learning model was better than students who got the conventional learning model. Continued the results of processing attitude data using the One Sample T-Test with a significance level of 0.05 and tested by one party, namely the right party test, it was obtained that the p-valued value = 0.00 < α = 0.05, then H0: μ0 = 3.00 was rejected and Ha: μ0 > 3.00 was accepted, so it can be concluded that students are positive towards the use of the Mind Mapping learning model in mathematics learning is more than 3. (1) students' mathematical problem-solving skills using the Mind Mapping learning model are better than conventional learning. (2) students are positive about learning mathematics by using the Mind Mapping learning model.